Breathe the sky - Hazen, Michelle (Jove, 2020)
"Two strangers start out saving animals and end up rescuing each other in this heartwarming romance from the author of Unbreak Me. Mari Tucker is a wildlife biologist who scoops bunnies and endangered tortoises out of harm's way on construction sites. Still haunted by her past, she takes the most remote jobs in the Mojave Desert to avoid people and hide from her ex. It's a simple, quiet life filled with sweet animals and solar-powered baking until she ends up assigned to Jack Wyatt's crew. Construction foreman Jack Wyatt's loud, foul-mouthed temper keeps even the most rugged of men on his crew in line. No mistake is overlooked, because out in the desert it could mean life or death. In his opinion, the job site is no place for sensitive biologists, especially one as shy as Mari. But instead of wilting from the heat and hard work, Mari wins over Jack and his crew one homemade brownie at a time. Jack and Mari find a comfortable rhythm, building a friendship that's rare for both of them. After Jack's rocky childhood, they have more in common than they'd imagined. But even the Mojave sun can't chase away the shadows when the past is determined to track them down..."--